2011
DOI: 10.1136/bjo.2009.177972
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum of Fork-Head Transcriptional Factor Gene (FOXL2) in Indian Blepharophimosis Ptosis Epicanthus Inversus Syndrome (BPES) patients

Abstract: Mutations in the region downstream of the fork-head domain were predominantly responsible for BPES among Indian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These findings are reminiscent of PCOS, the most common ovarian dysfunction in women in their reproductive life, as suggested by Murphy [61]. Although a link between FOXL2 dysregulation and PCOS has not yet been demonstrated clearly in humans, constitutional FOXL2 mutations found in syndromic POF (BPES type I) associated withandrogen-induced hirsutism [61], and in a BPES patient with reported PCOS [62] might represent first hints. However, it should be noted that PCOS is very common in the general population (6-10%) and can go up to 52% in the Indian subcontinent [63,64].…”
Section: Foxl2 Impairment In Other Diseasesmentioning
confidence: 89%
“…These findings are reminiscent of PCOS, the most common ovarian dysfunction in women in their reproductive life, as suggested by Murphy [61]. Although a link between FOXL2 dysregulation and PCOS has not yet been demonstrated clearly in humans, constitutional FOXL2 mutations found in syndromic POF (BPES type I) associated withandrogen-induced hirsutism [61], and in a BPES patient with reported PCOS [62] might represent first hints. However, it should be noted that PCOS is very common in the general population (6-10%) and can go up to 52% in the Indian subcontinent [63,64].…”
Section: Foxl2 Impairment In Other Diseasesmentioning
confidence: 89%
“…The low prevalence of FOXL2 mutation in our patient population could be partly attributed to a different ethnic population and very few cases with a positive family history. Previous genetic studies on Indian BPES patients have been reported from the southern parts of India, [15][16][17] where the population is ethnically different from Northern India and a high number of consanguineous marriages are found, resulting in a different mutation spectrum. In our study, seven out of nine familial cases (77%) were found to be positive for genetic defects, which is consistent with western studies in which 72% of clinically diagnosed BPES cases have a mutation in the FOXL2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there have been very few genetic studies so far on the pattern of genetic abnormalities found in BPES cases in the Indian population. [15][16][17] Therefore, we undertook a prospective study at our center to evaluate BPES patients with respect to clinical, genetic, and imaging findings.…”
Section: Methodsmentioning
confidence: 99%
“…Goats that are recessive for this mutation show XX female-to-male sex reversal [Pailhoux et al, 2001]. Two recessive mutations have been reported, associated with BPES and ovarian failure, a phenotype identical to the dominant heterozygous mutations with no evidence of virilization [Nallathambi et al, 2007;Kaur et al, 2011]. However, in both cases, it is likely that the mutant alleles are hypomorphic, retaining some biological activity, so the phenotype of a true FOXL2 null mutation in the human remains to be determined.…”
Section: Gene Mutations Associated With 46xx Srynegative Testicular mentioning
confidence: 99%